Challenges faced by service users attending substance abuse aftercare programs in selected treatment centres in South Africa. - Peter Singwane, Thembinkosi; Xolile Lukhele, Bridget; Makgopo, Cedrick Molatelo (Student’s Journal of Health Research Africa, 2026)
Background: Substance use disorders (SUDs) remain a significant public health and social welfare concern in South Africa, with relapse following treatment continuing to undermine recovery outcomes. While considerable scholarly and policy attention has been directed towards treatment and rehabilitation programmes, aftercare services remain comparatively under-explored, particularly from the perspectives of service users themselves. Aftercare programmes are intended to support individuals as they transition from structured treatment environments back into their communities; however, limited empirical evidence exists regarding the challenges service users encounter during this critical stage of recovery. Methodology: This qualitative study explored the social, economic, emotional, and psychological challenges experienced by service users attending substance abuse aftercare programmes at selected treatment centres in Limpopo and Mpumalanga provinces. A purposive sample of ten participants currently enrolled in aftercare programmes was recruited. Data were collected through semi-structured interviews that allowed participants to reflect on their lived experiences of recovery following rehabilitation. The interviews were audio-recorded, transcribed verbatim, and analysed using thematic analysis to identify recurring patterns, meanings, and contextual factors shaping participants’ recovery experiences. Results: The findings indicate that, despite completing rehabilitation, service users continue to experience multiple and intersecting challenges that threaten sustained recovery. Prominent challenges included persistent social stigma, limited employment opportunities, strained family relationships, and ongoing emotional distress. Participants also reported psychological difficulties such as anxiety, depressive symptoms, and unresolved trauma, which often intensified feelings of vulnerability during reintegration into community life. These factors collectively heightened the risk of relapse. Conclusion: The study highlights that recovery from substance use disorders extends far beyond the completion of formal treatment and requires sustained psychosocial and structural support. Recommendations: Strengthening aftercare services through integrated psychosocial support, skills development initiatives, and community-based recovery interventions is essential for promoting long-term recovery and reducing relapse among individuals with substance use disorders in South Africa.